Spatial configurations in urban environmental analysis – The role of the heat island effect - Adriano Magliocco; Gabriele Oneto (Agathón)
The module, a system’s unit of dimension, is a concept that is still useful in analysing and planning cities. The Heat Island Effect is the occasion for inquiring about how to develop methodologies for reading and understanding urban systems by following reproducible and univocal principles. Starting from environmental temperature data, often representative of portions of squared urban grids, some spatial analytical methodologies are proposed and applied to two European cities: Genoa and Munich. Using the Local Climate Zones, a first map is defined at the urban level using a squared module. Subsequent maps question the infrastructural and morphological systems using graphs and tessellations. The urban planner that operates on complex systems can place these tools beside their analyses, verifying and examining urban environments.